The Transformative Forces of Migration: Refugees and the Re-Configuration of Migration Societies - Hamann, Ulrike (2018)
In this thematic issue, we attempt to show how migrations transform societies at the local and micro level by focusing on how migrants and refugees navigate within different migration regimes. We pay particular attention to the specific formation of the migration regimes that these countries adopt, which structure the conditions of the economic, racialised, gendered, and sexualized violence and exploitation during migration processes. This interactive process of social transformation shapes individual experiences while also being shaped by them. We aim to contribute to the most recent and challenging question of what kind of political and social changes can be observed and how to frame these changes theoretically if we look at local levels while focusing on struggles for recognition, rights, and urban space. We bring in a cross-country comparative perspective, ranging from Canada, Chile, Spain, Sweden, Turkey, and to Germany in order to lay out similarities and differences in each case, within which our authors analyse these transformative forces of migration.